Toxicological Analysis and Interpretation in Cases of Suspected Drug-induced Organ Toxicity: Systematic Review - Tripathi , SK; Singh , RR; Singh, S; Yadav , PK (Journal of Indian Academy of Forensic Medicine, 2024)
When pharmacological drugs have negative effects on a particular organ or organ system, it is referred to as drug-induced organ toxicity. It  is crucial to correctly recognize and comprehend these toxicities to guarantee proper medical action and the mitigation of additional injury.  Through the identification of putative toxicological pathways, quantification of drug metabolites, and assessment of the connection  between drug exposure and organ damage, toxicological analysis plays a crucial part in this process. This study aims to identify the critical  elements of toxicological analysis of drug-induced organ toxicity, focusing on the importance of interdisciplinary collaboration for  reliable findings interpretation. A digital database was employed to conduct a literature and database search for this investigation. 8,530  results from Bullion Words were returned, and 7,360 sample articles were chosen. The sample was reduced for inspection by further  analysis to 1,170. 960 samples were disqualified due to download problems. After 210 articles were eliminated due to quality issues, 180  articles underwent full-text examination, and 33 papers (n=33) were ultimately chosen. Numerous methods, such as immunoassays,  chromatography, mass spectrometry, and molecular biology tests, are used in toxicological investigation when there is a suspicion that a  medication has caused organ toxicity. The target organ, the drug of interest, and the level of analytical sensitivity needed all play a role in  choosing the best analytical technique. Considerations for interpreting toxicological data include drug concentrations, the presence of  metabolites, pharmacokinetic characteristics, and the timing of the beginning of organ damage. In situations of suspected drug-induced  organ toxicity, accurate toxicological analysis and interpretation are essential for effective diagnosis, therapy, and medico legal  investigations. Amore accurate diagnosis of drug-related organ damage is made possible by combining cutting-edge analytical methods,  including mass spectrometry, with thorough clinical and pathological examinations. We will be able to comprehend and function more  effectively in this crucial field of toxicology as a result of ongoing study, technological developments, and cooperative efforts among  specialists from many disciplines.
Keywords: Analytical techniques; Biological samples; Organ toxicity; Reliability; Suspected cases; Toxicological tests; etc